Corrosion Investigation On Dissimilar Friction Stir Welded Plates - Abdul Rahim, Muhamad Azrin Syaqir (2018)
For this project, corrosion behavior of welded joint of AA7075-T6 and AA6061-T6 aluminum alloy using friction stir welding process will be studied. Corrosion property of welded joint will be investigated using Polarization Method. Solution of 3.5mol NaCl aqueous solution with pH = 6.5 at a room temperature is used during experimentation. This experiment is done to studies the corrosion morphology in the weld region after corrosion test. Microstructure properties of parent alloy, nugget zone, thermomechanically affected zone(TMAZ) and heat affected zone(HAZ) all been analyzed using Scanning electron microscopy at 200 magnification level. Results show that friction stir welding process give huge effect to corrosion resistance which associate with the dissolution of intermetallic particles. When intermetallic particles distributed all through the surface of weld region, it will increase the galvanic corrosion. However, most part of weld region and parent alloy are prone to intergranular corrosion and pitting.